Rheological and structural details of biocidal iPP-TiO2 nanocomposites - Serrano, Cristina (2012)
Nanocomposites obtained from incorporation of TiO2 nanoparticles in different amounts, ranging from 0.5 to 5 wt.%, into an isotactic polypropylene (iPP) matrix are achieved via a straightforward and cost-effective melting process. These materials exhibit a powerful germicide capability over a wide variety of regular bacteria and other microorganisms widely present in the environment that cause infections and serious illness. The iPP-TiO2 nanocomposites show similar or improved structural characteristics than those of the pure iPP matrix and aspects as important as processability and final mechanical performance seem to be not affected because of the incorporation of these TiO2 nanoparticles. Validation of time–temperature superposition of the molten polymers is observed within the temperature range analyzed. On the other hand, the α polymorph is the one primarily attained for these specimens. Crystallinity and most probable crystallite size are slightly dependent on TiO2 content, both increasing as oxide composition is enlarged.